The production of eggs by gastrointestinal nematodes in Nellore cows, during the peri-parturient period - Bianchin, Ivo; Honer, Michael Robin; Curvo, João Baptista Esmela (Pesquisa Agropecuaria Brasileira, 2014)
An evaluation was made of the influence of the peri-parturient period on the counts of eggs of nematodes in the faeces of beef cattle. Thirty-two Nellore pregnant cows were used, of which 8 with the first calf, 12 with the second and 12 with the third calf, all calving in October. To determine the number of eggs per gram of faeces (EPG) and larvaecultures, one sample of faeces was collected before calving (aproximately fifteen days before), one sample at calving and six weekly samples post calving. There was no significant interaction between the number of calves and the EPG counts in the different samples. No significant difference was observed in the EPG counts before and after calving, although there was a tendency to an increase on the day of calving and during two weeks afterwards. Cows with first calf showed mean EPG higher than those with second and third calves, both before and after calving (P<0.05). Cooperia sp. contributed most to the rise in mean EPG. Taking into consideration the increase in EPG of cows, and epidemiological studies previously carried out, it is recommended that cows be dosed in the months of July or August.